2008
DOI: 10.1007/s11144-008-5236-3
|View full text |Cite
|
Sign up to set email alerts
|

A simple preparation method of eggshell Ni/MgO-Al2O3 catalyst for partial oxidation of methane

Abstract: A simple method to prepare eggshell Ni/MgO-Al 2 O 3 catalyst was developed. In partial oxidation of methane, eggshell Ni/MgO-Al 2 O 3 showed better reactivity and stability than the uniform one, even than eggshell Ni/Al 2 O 3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 15 publications
(12 reference statements)
3
10
0
Order By: Relevance
“…xMg/Al pellets (not shown) revealed that the decomposition of the impregnated nitrate precursor occurred in the temperature range 300-400 C. In fact, in correspondence of weight loss occurring in this temperature range, the typical IR bands of NO 2 were observed at 1580-1650 cm À1 . That is in agreement with results of Qiu et al 29 who found that IR signals of nitrate groups from Mg(NO 3 ) 2 precursor used for impregnation of g-Al 2 O 3 spheres were still present if the composite support was calcined at 350 C whereas they disappeared aer heating at 450 C. In our experiment at 550-600 C a stable weight was achieved thus ensuring that nitrates are totally decomposed at the calcination temperature.…”
Section: Tg-ftir Analysis During the Calcination Treatment Of Driedsupporting
confidence: 93%
See 2 more Smart Citations
“…xMg/Al pellets (not shown) revealed that the decomposition of the impregnated nitrate precursor occurred in the temperature range 300-400 C. In fact, in correspondence of weight loss occurring in this temperature range, the typical IR bands of NO 2 were observed at 1580-1650 cm À1 . That is in agreement with results of Qiu et al 29 who found that IR signals of nitrate groups from Mg(NO 3 ) 2 precursor used for impregnation of g-Al 2 O 3 spheres were still present if the composite support was calcined at 350 C whereas they disappeared aer heating at 450 C. In our experiment at 550-600 C a stable weight was achieved thus ensuring that nitrates are totally decomposed at the calcination temperature.…”
Section: Tg-ftir Analysis During the Calcination Treatment Of Driedsupporting
confidence: 93%
“…Some authors reported the preparation of Ni-based catalysts with an egg-shell metal distribution purposely obtained for catalysis for very fast reaction with mass transfer limitations. [29][30][31] In particular, Qiu et al dispersed a Ni layer onto MgO/Al 2 O 3 spheres pre-calcined at different temperatures. 29 In this work we set out to investigate the preparation and characterization of Ni and Ru on MgO-coated g-Al 2 O 3 pellets as structured catalysts for the ethanol coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…POM is a very fast reaction [6]. The inner diffusion is very important for the catalysts with the diameter of about 1.5 mm, and so the eggshell catalysts show better catalytic performance [8]. Besides the nickel distribution, the pore structure of the catalysts also affects the catalyst activity.…”
Section: The Formation Of J-al 2 O 3 H-al 2 O 3 and A-al 2 O 3 Can mentioning
confidence: 99%
“…As a basic promoter, MgO also favors decreasing coke deposition through eliminating acidic sites and promoting CO 2 adsorption [5,7]. Recently, we have prepared the MgO promoted eggshell Ni/Al 2 O 3 catalyst, which also exhibited better performance than eggshell Ni/Al 2 O 3 catalysts [8]. Because POM is a very fast reaction and can fulfill in a few milliseconds inside a small volume catalytic bed [9,10], the inner diffusion affects strongly the catalytic performance for the Ni/Al 2 O 3 catalysts with a diameter of about 1.5 mm [11].…”
Section: Introductionmentioning
confidence: 99%